Impact of Neo-Liberalism and Globalization - Majumdar, Ananda (ABC Journal of Advanced Research, 2018)
From the perspective of neoliberal globalization, the purpose of this essay is to explore and understand the social and educational phenomenon of student’s migration from India to Canada, such as; Neoliberal globalization and its impact on higher education; Student mobility from India to Canada on their decision to pursue for higher studies; Indian and Canadian policies on international education and students; Factors Facilitating the success of overseas studies and the experience at the University of Alberta; Global Citizenship existence on international student. It is an expression of historical way of South American colonial, post-colonial, neo-colonial ideologies that are existed with present form of globalized and neo liberal ideologies to share thoughts within people all over the world but these present of universal thought, expression was not easy going in the past. However, a complete descriptions of ideologies which is active in present world order through deafening socialist ideologies. I would like to pursue my PhD in International Development and the ideas of liberalism, neo liberalism, colonialism, neo colonialism, globalization, will help me to understand global development by those ideologies. However, it has critical reviews, controversial thoughts but it has positive sides as well and I always prefer on positivism of globalization and neo liberalism through which world can be turns into one world order economically, I am hopeful.